Sifat Hipoglisemik dan Hipolipdemik Kacang Kapri (Pisum sativum LINN) dan Kedelai (Glicine max MERR) pada Tikus Sprague Dawley Diabetik Induksi Alliksan - Yustinus Marsono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Hypoglycemic and hypolidemic properties of Edible podded peas (Pisium sativum LINN) and Soy bean (Glycine max MERR) were evaluated in alloxan-induced diabetic rats. The objectives of this research were to investigate the effects of these legumes on serum glucose, total cholesterol and triacyl glycerol in alloxan-induced diabetic rats. Thirty male Sprague-Dawley (SD) rats (250-300 g) were provided and divided into three groups of ten rats. They were diabetic induced by twice intramuscular injection of alloxan (80 mg/Kg of body weight), then fed with three different diets i.e. Standard (ST), (2) Edible Podded peas (EP) and Soybean (SB) for 28 days. The legumes provided 20 % calorie of total duet calorie. Concentration of serum glucose, total cholesterol and tracyl glycerol were measured before injection and diet intervention (0 day and day 17th) and were monitored in the middle and at the end of diet intervention (day 31st and 45th). It was found that alloxan injection increased serum glucose concentration from 63.5 mg/dL to 281.4 mg/dL, total cholesterol and triacyl glycerol concentration increased from 90.7 mg/dL to 136.6 mg/dL and from 108 mg/dL to 147.5 mg/dL, respectively. In 28 days of diet intervention, EP and SB diets decreased the serum glucose concentration by 145.5 mg/dL (67%) and 142.1 mg/dL (65%), respectively, compared to 125.3 mg/dL (57%) in the ST diet. Total cholesterol decreased by 31% and 27% for EP and SB groups. respectively but only 17% for ST rats. Intervention of the diets also decreased concentration of triacyl glycerol by 9% and 5% for EP and SB diets, respectivelym but increased by 6% for standard (ST) diet.